Mechanical and Morphological Properties of Uniaxially Oriented and Heat-Treated Poly(Lactic Acid)/Poly(Butylene Adipate-Co-Terephthalate) Blends - Gergely Csézi; Tamás Tábi (Advances in Polymer Technology)
This paper investigates the effect of poly(butylene adipate-co-terephthalate) (PBAT) on the mechanical and morphological properties of poly(lactic acid) (PLA) when the PLA is blended with 10%, 20%, and 30% PBAT and subjected to different draw ratios (DRs), followed by annealing at a fixed length. Results indicate that PBAT functions more as a strengthening agent than a toughening agent when the blend is drawn. Furthermore, both undrawn and most drawn samples exhibit higher crystallinity and lower cold crystallization temperatures (Tcc) (in proportion to PBAT ratio) compared to the unblended material, with crystallinity equilibrating at the highest measured draw ratio (DR) of 4, as determined by differential scanning calorimetry (DSC). The crystallinity of the annealed samples equilibrates at 45%–47%, demonstrating the effectiveness of heat treatment at the cold crystallization temperatures of the samples, as measured by DSC, which decreases with increasing DR. However, X-ray diffraction (XRD) results show that heat treatment at the original Tcc, specific to the undrawn PLA, results in higher crystal orientation.